FRAMING GERAKAN FORUM MASYARAKAT MINANGKABAU DAN ADVOKASI KEBIJAKAN INVESTASI DI KOTA PADANG: KASUS PT. LIPPO TBK. - Wira Hospita; Aidinil Zetra; Afrizal Afrizal (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2018)
Social movements are a typical form of community activism, where there is a form of collective action with a clear conflictual orientation and bound by a sense of solidarity and a strong collective identity. This article highlights the success strategies of the Minangkabau community movement that are members of the Minangkabau Community Forum (FMM) rejecting Siloam's investment, and advocating for the policies of the Padang City Government (Pemko) regarding the principle permit for utilization of room number 650.44 / Bapeda / II-2013. FMM assesses that the City Government's policy has threatened the values of the customs and religion, mobilizing collective action based on cultural issues, where Adat Bersandi Sarak, Sarak Bersandi Kitabullah is used as the main frame to mobilize the community to support advocacy.